2005
DOI: 10.1158/1078-0432.ccr-04-2310
|View full text |Cite
|
Sign up to set email alerts
|

NHS76/PEP2, a Fully Human Vasopermeability-Enhancing Agent to Increase The Uptake and Efficacy of Cancer Chemotherapy

Abstract: Purpose: Previously, we have shown that the attachment of interleukin 2 (IL-2) to a tumortargeting antibody can produce a 4-fold enhancement in the uptake of antibodies and drugs in tumors. More recently, we discovered that a 37-amino-acid linear sequence of IL-2 designated vasopermeability-enhancing peptide (PEP), contained the vasopermeability activity of IL-2, and could be used after linkage to tumor-targeting antibodies to produce the same enhancement of drugs and antibodies in tumors. We now describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…Its fusion protein with antibody NHS76 (NHS76/PEP) showed an increased uptake compared with NHS76 alone. Pretreatment of animals with NHS/PEP also augmented the therapeutic effect of several drugs (doxorubicin, Taxol, vinblastine, etoposide, and 5-fluorouracil) within a 2-hour interval (27).…”
Section: Discussionmentioning
confidence: 96%
“…Its fusion protein with antibody NHS76 (NHS76/PEP) showed an increased uptake compared with NHS76 alone. Pretreatment of animals with NHS/PEP also augmented the therapeutic effect of several drugs (doxorubicin, Taxol, vinblastine, etoposide, and 5-fluorouracil) within a 2-hour interval (27).…”
Section: Discussionmentioning
confidence: 96%
“…These signaling molecules increase the physical permeability of vasculature by inducing the formation of fenestrations within endothelial cells or increasing the size of intercellular gaps [133][134][135]. Epstein and coworkers have demonstrated that systemic administration of IL-2 peptides fused to tumor targeting antibodies can specifically increase permeability of the tumor vasculature leading to increased tumor uptake and therapeutic efficacy of subsequently administered drugs [136,137]. In contrast, Halin et al found that pretreatment of tumor bearing mice with a tumor targeting scFv-VEGF fusion only improved uptake of subsequently administered drugs moderately and at high concentrations [138].…”
Section: Increasing Transcapillary Fluxmentioning
confidence: 99%
“…Using a 2-h pretreatment, an optimal dose of NHS76/PEP2 (30 μg) induced greatly increased and specific tumor accumulation of the mAb B72.3. 86 This approach increased also tumor accumulation and therapeutic efficacy of the chemotherapeutic drugs etoposide, doxorubicin, paclitaxel (Taxol ® ), docetaxel (Taxotere ® ), 5-fluorouracil, or vinblastine. The same group had previously shown that conjugation of tumor necrosis factor (TNF)-α to the tumor necrosis-targeting mAb TNT-1 caused a three-fold increase of the tumor uptake of the F(ab') 2 fragment of the same antibody.…”
Section: Approaches To Improve Tumor Accumulation and Interactions Bementioning
confidence: 99%